An improved technique for Morgagnian cataract phacoemulsification - E. S. Pirogova; O. L. Fabrikantov; S. I. Nikolashin (Российский офтальмологический журнал)
Purpose: to develop new approaches to Morgagnian cataract surgery by optimizing the phacoemulsification technique and reducing the risk of surgical complications.Material and methods. 22 patients (22 eyes) with hypermature Morgagnian cataract were divided into 2 groups. The main group I included 11 patients who underwent surgery according to the PEC technology using iridocapsular retractors, an intracapsular ring and the scaffold technique with the last nucleus fragment relocated into the anterior chamber. The comparison group II included 11 patients with PEC and IOL implantation using iridocapsular retractors and an intracapsular ring with no scaffold technique involved. In 7 patients of group I, the lens nucleus was considered “large” and in 4 patients, “small”. In 8 patients of group II, the lens nucleus was considered “large” and in 3 patients, “small”.Results. After 6 months, BCVA in group I was 0.60, whilst in group II it was 0.70. IOP in group I averaged 12.9 mm Hg, while in group II it averaged 17.90 mm Hg. The endothelial cell density (CD) in group I decreased by 241 cells and amounted to 2012.0 cells/mm2 , the endothelial cell loss was 10.70%, while in group II CD loss was greater. It dropped by 377 cells (15.60%) and amounted to 2039 cells/mm2 .Conclusions. The severity of involutional changes in the ligamentous apparatus of the lens in Morgagnian cataract was found to depend on the nucleus size. A working classification of Morganian cataract by the nucleus size has been proposed. The use of scaffold technique with the relocation of the last fragment into the anterior chamber made it possible to reduce the share of surgical complications to 18.18%. During phacoemulsification of Morgagnian cataract with small nuclei, surgical complications took place in both group I and II, which necessitates further improvement of the existing surgical technique of this type of pathology.